Performing English with a Postcolonial Accent: Ethnographic Narrativ es from Mexico - Newman, Lesley (Colombian Applied Linguistics Journal, 2013)
Angeles Clemente and Michael Higgins is a textured portrait of Oaxacan students enrolled in a university English program (the Centro de Idiomas, or Centro). In it, the authors show us their students’ relationship to widely-accepted notions of English ownership, English-speaker legitimacy, and the global spread of English. It is important that more professionals in the field of applied linguistics examine these relationships. Clemente and Higgins do so from an interdisciplinary, theoretical background without isolating the reader from outside those fields.